Does duration of physical activity bouts matter for adiposity and metabolic syndrome? A cross-sectional study of older British men. Issue 1 (December 2016) - Jefferis, Barbara; Parsons, Tessa; Sartini, Claudio; Ash, Sarah; Lennon, Lucy; Wannamethee, S.; Lee, I-Min; Whincup, Peter
Abstract Background Older adults have low physical activity(PA) and high sedentary behaviour(SB) levels. We investigate how total volume and specific patterns of moderate to vigorous PA(MVPA), light PA(LPA) and SB are related to adiposity and metabolic syndrome (MS). Then, with reference to physical activity guidelines which encourage MVPA in bouts > =10 min and avoiding "long" sedentary bouts, we investigate whether accumulating PA and SB in bouts of different defined durations are differently associated with these outcomes. Methods Cross-sectional study of men (71–91 years) recruited in UK primary care centres. Nurses made physical measures (weight, height, bio-impedance, blood pressure) and took fasting blood samples. 1528/3137 (49 %) surviving men had ≥3 valid days (≥600 min) accelerometer data. 450 men with pre-existing chronic disease were excluded. 1009/1078 (93.6 %) had complete covariate data. Results Men (n = 1009, mean age 78.5(SD 4.7) years) spent 612(SD 83), 202(SD 64) and 42(SD 33) minutes in SB, LIPA and MVPA respectively. Each additional 30 min/day of SB and MVPA were associated with 0.32 (95 % CI 0.23, 0.40)Kg/m2 higher Body Mass Index (BMI) and −0.72(−0.93, −0.51) lower BMI Kg/m2 respectively. Patterns for waist circumference (WC), fat mass index (FMI), fasting insulin and MS were similar. MVPA in bouts lasting <10 min or ≥10 min duration were not associated differently with outcomes. In models adjusted for total MVPA, each minute accumulated in SB bouts lasting 1–15 min was associated with lower BMI −0.012 kg/m2, WC −0.029 cm, and OR 0.989 for MS (allp < 0.05), and coefficients for LPA bouts 1–9 min were very similar in separate models adjusted for total MVPA. Minutes accumulated in SB bouts 1–15 min and LPA bouts 1–9 min were correlated, r = 0.62. Conclusions Objectively measured MVPA, LPA and SB were all associated with lower adiposity and metabolic risk. The beneficial associations of LPA are encouraging for older adults for whom initiating MVPA and maintaining bouts lasting ≥10 min may be particularly challenging. Findings that short bouts of LPA (1–9 min) and SB (1–15 min), but that all MVPA, not just MVPA accumulated in bouts ≥10 min were associated with lower adiposity and better metabolic health could help refine older adult PA guidelines.